Aging-regulated TUG1 is dispensable for endothelial cell function. - Anna Theresa Gimbel; Susanne Koziarek; Kosta Theodorou; Jana Felicitas Schulz; Laura Stanicek; Veerle Kremer; Tamer Ali; Stefan Günther; Sandeep Kumar; Hanjoong Jo; Norbert Hübner; Lars Maegdefessel; et al. (PLoS ONE)
The evolutionary conserved Taurine Upregulated Gene 1 (TUG1) is a ubiquitously expressed gene that is one of the highest expressed genes in human and rodent endothelial cells (ECs). We here show that TUG1 expression decreases significantly in aging mouse carotid artery ECs and human ECs in vitro, indicating a potential role in the aging endothelial vasculature system. We therefore investigated if, and how, TUG1 might function in aging ECs, but despite extensive phenotyping found no alterations in basal EC proliferation, apoptosis, barrier function, migration, mitochondrial function, or monocyte adhesion upon TUG1 silencing in vitro. TUG1 knockdown did slightly and significantly decrease cumulative sprout length upon vascular endothelial growth factor A stimulation in human umbilical vein endothelial cells (HUVECs), though TUG1-silenced HUVECs displayed no transcriptome-wide mRNA expression changes explaining this effect. Further, ectopic expression of the highly conserved and recently discovered 153 amino acid protein translated from certain TUG1 transcript isoforms did not alter angiogenic sprouting in vitro. Our data show that, despite a high expression and strong evolutionary conservation of both the TUG1 locus and the protein sequence it encodes, TUG1 does not seem to play a major role in basic endothelial cell function.